PSIKOEDUKASI MANAGEMENT CONFLICT PADA KARYAWAN PERUSAHAAN CV KPI - Alfridha Septiany Said; Asrini; Iftinan Maftuha; Harlina Hamid (CV. Multi Kreasi Media, 2023)
The relationship between employees with other employees in a company is expected to remain cooperative. But in reality, in CV KPI there are often differences of opinion to achieve a certain goal. Therefore, it takes an effort or intervention to assist employees in managing conflict properly. So that conflicts that will occur in the future will not become an obstacle for the company to develop. The how to manage conflict seminar is a seminar that contains employee tips in managing existing conflicts and how a conflict results in a compromise that can mutually improve performance in a company. This psychoeducation aims to provide an understanding of the importance of conflict management for CV KPI employees, with the hope that this understanding of conflict management can serve as a guideline for employees to resolve conflicts properly in the work environment. The results of the seminar show that providing psychoeducational seminars is quite helpful for employees because this can be used as a self-reminder in managing a conflict based on corporate culture and creates insight that not all conflicts that occur within the company are negative, but sometimes these conflicts have a positive impact on company development.